Atividade antimicrobiana de compostos bioativos naturais na conservação pós-colheita de manga - Jardinetti, Virlene do Amaral (2013)
The use of natural bioactive compounds has shown efficiency in the pathogens control and conservation postharvest fruits. This study aimed to evaluate the effects of derivatives of Cymbopogon citratus and Moringa oleifera in growth and sporulation of Colletotrichum gloeosporioides and in conservation of postharvest mango fruits as well as to determine the content and composition of essential oil extracted of fresh dried lemongrass leaves collected in different seasons. The seasonal study examined the interference of the collection period on the content and chemical composition of essential oil obtained by hidrodistillation and biological activity about C. gloeosporiodes in the concentrations 0, 0,025, 0,05, 0,075 e 0,l. In vitro test with aqueous crude extracts of leaves and Moringa oleifera seeds (l0%), C. citratus essential oil (0.075%), M oleifera oil (0.075%); mixture of M oleifera oil and essential oil C. citratus (0.075% and 0.075%), procloraz (0.05%) and Tween 20 (0.025%) were assessed for inhibition of mycelia growth (IMG), the rate of mycelia growth rates (MGIR) and sporulation of the pathogen that causes anthracnose. The control consisted of plates containing only ADP (agar-dextrose-potato). In the postharvest the fruits were treated by immersion (three minutes), with aqueous crude extracts of leaves and seeds of M. oleifera (25%); C. citratus hidrolate (25%); M oleifera oil (l%); mixture of M. oleifera oil plus hidrolate (l% and 25%), procloraz (0,ll%) and Tween 20 (0,l%), verifying the effect of these treatments in the mango fruits postharvest conservation. The control consisted of the immersion of fruits in distillated water. The treated fruits were maintained under environmental conditions, arranged in plastic cubes, being submitted to initial evaluation (date of experiment installation), two partial evaluation and evaluation in the fourteenth day. Mass, volume, color, soluble solids (Brix°), pH, titratable acidity (AT) and disease incidence were evaluated. The obtained results were submitted to statistical analysis at SISVAR program, with a significant level of 5%. In the seasonal study, the geranial, neral and myrcene presented as majority chemicals at all extractions, observing interference of harvest times in the content and chemical composition of the essential oil. However, these variations did not affect the fungitoxicity of C. citratus over the phytopathogen C. gloeosporioides. In the in vitro test, it was verified that C. citratus essential oil and the mixture of essential oil plus M 0leU"era oil inhibited significantly the growth and sporulation of the phytopathogen, when compared to the control. In the in vivo evaluations with postharvest mango fruits, with derivative products of M. oleifera species, mainly the oil, has proved to be promising in the conservation of mango fruits "Tommy Atkins" in the postharvest, reducing the process of fruits maturation.